PROSUMER ENERGY DIFFUSION DETERMINANTS IN ASSOCIATION WITH LOCAL PLANS OF LOW EMISSION - SMOG - REDUCTION - Kuceba, Robert; Zawada, Marcin; Kowalik, Jan (PEOPLE: International Journal of Social Sciences, 2021)
The cognitive focus of the article concerns the measurement and aggregation of relationships between the diffusion of prosumer energy development and the effectiveness of implementing local Plans of Low Emissions Reduction. In this context, the Authors have justified that local actions in the area of low emission prevention (smog - unusual atmospheric phenomenon) are fully converged with the activities of prosumers, producing energy, among others, in order to meet their own needs. On the basis of the literature query and interviews in a group of managers of the energy and environmental management in territorial units - local perspective (in the selected EU country), levels of energy prosumer transformation have been determined in relation to the measures in the scope of low emission prevention.